Surfactant Induced Eriochrome Blue Black B-Metal Ion Interactions: Complexation and Analytical Studies - Mahakalkar, A.S. (Asian Journal of Chemistry, 2010)
The chelation reactions of certain lanthanides and actinides in the presence of cetyltrimethylammonium bromide (CTAB) have been studied in details. The complexes show a large bathochromic shift. The composition of the chelates of uranium, thorium, yttrium and europium with eriochrome blue black B was found to be 1 : 2 both in the absence and presence of CTAB. The stability constants of the complexes have been evaluated. The values of stability constants of ternary complexes of Th4+ and UO22+ have been found to be considerably increased in comparison to their corresponding binary complexes. The increased stability of ternary complex may be due to the stabilization of ternary complex in the surrounding atmosphere of cationic micelles of CTAB. The studies were extended to the analytical aspects of the complex equilibria and a suitable procedure has been recommended for the sensitive spectrophotometric determinations of metal ions under study. The effects of foreign ions on the systems was studied in the presence of large number of cations and anions. The extent of bathochromic shift in lmax, considerable increase in the sensitivity and high stability of the complexes in the presence of CTAB shows the utility of this micelle forming cationic surfactant in the sensitization of colour reaction. The range of concentration for adherence to Beer's law and the effective photo range was calculated. The utility of these proposed methods have been established by evaluating the precision and the accuracy by employing suitable statistical methods.